The Retrosplenial Cortex: Intrinsic Connectivity and Connections with the (Para)Hippocampal Region in the Rat. An Interactive Connectome - Sugar, Jorgen; Witter, Menno P.; van Strien, Niels; Cappaert, Natalie (Frontiers in Neuroinformatics, 2011)
A connectome is an indispensable tool for brain researchers, since it quickly provides comprehensive knowledge of the brain’s anatomical connections. Such knowledge lies at the basis of understanding network functions. Our first comprehensive and interactive account of brain connections comprised the rat hippocampal-parahippocampal network. We have now added all anatomical connections with the retrosplenial cortex as well as the intrinsic connections of this region, because of the interesting functional overlap between these brain regions. The retrosplenial cortex is involved in a variety of cognitive tasks including memory, navigation and prospective thinking, yet the exact role of the retrosplenial cortex and the functional differences between its subdivisions remain elusive. The connectome presented here may help to define this role by providing an unprecedented interactive and searchable overview of all connections within and between the rat retrosplenial cortex, parahippocampal region and hippocampal formation.